Каникулы Бонифация: сказка / Ф. С. Хитрук ; худ. : С. Бордюг - Хитрук Федор С. (Планета детства, 2001)
Экземпляры: 1, 10 ф. (12.11.08г.) / Инвентарный номер: 44804 / Цена: / Сис.шифр: Д / Авт.знак: Х 52 / ББК: Д